2016
DOI: 10.1128/microbiolspec.vmbf-0024-2015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Function of Type IV Secretion During Infection of the Human Host

Abstract: Bacterial pathogens employ type IV secretion systems (T4SSs) for various purposes to aid in survival and proliferation in eukaryotic host. One large T4SS subfamily, the conjugation systems, confers a selective advantage to the invading pathogen in clinical settings through dissemination of antibiotic resistance genes and virulence traits. Besides their intrinsic importance as principle contributors to the emergence of multiply drug-resistant ‘superbugs’, detailed studies of these highly tractable systems have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 240 publications
(313 reference statements)
0
38
0
Order By: Relevance
“…In regard to the proapoptotic effect that the K279a VirB/D4 T4SS has on macrophages, it is tempting to speculate that this function evolved as a result of S. maltophilia interacting with predatory protozoans (amoebae) in nature (113)(114)(115)(116)(117). Despite demonstrating the importance of the S. maltophilia T4SS in influ- encing the death of other cells, we do not believe that this is the only function of this VirB/D4 T4SS, given what is known about T4SS in general (35)(36)(37).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In regard to the proapoptotic effect that the K279a VirB/D4 T4SS has on macrophages, it is tempting to speculate that this function evolved as a result of S. maltophilia interacting with predatory protozoans (amoebae) in nature (113)(114)(115)(116)(117). Despite demonstrating the importance of the S. maltophilia T4SS in influ- encing the death of other cells, we do not believe that this is the only function of this VirB/D4 T4SS, given what is known about T4SS in general (35)(36)(37).…”
Section: Discussionmentioning
confidence: 84%
“…Thus, a recent bioinformatic study encompassing a very wide variety of organisms and their secretion systems suggested that S. maltophilia K279a encodes more than 25 putative T4SS effectors (125). Such a sized output is entirely compatible with the output of known T4SSs, which ranges from 1 (B. pertussis and H. pylori) to ϳ7 to 25 (Bartonella, Brucella, Anaplasma, and Ehrlichia) to Ͼ140 (Coxiella and Legionella) (35,45,46,49,126). Moreover, it could account for the multiple effects of the VirB/D4 system that we have defined in our study as well as other potential functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of one large T4SS subfamily, designated as conjugation systems, mediate the propagation of mobile genetic elements (MGEs) and their collection of associated antibiotic resistance genes, virulence determinants and other fitness traits among bacterial populations (de la Cruz et al, 2010). Those of a second large subfamily evolved from ancestral conjugation systems for the specialized purpose of delivering effector proteins into eukaryotic target cells to aid in infection processes (Ben-Tekaya et al, 2013;Gonzalez-Rivera et al, 2016;Sherwood and Roy, 2016). The T4SSs translocate their macromolecular cargoes to bacterial or eukaryotic target cells by a mechanism generally requiring direct cell-to-cell contact.…”
Section: Introductionmentioning
confidence: 99%
“…This T4SS subgroup is known to be one of the main mechanisms responsible of the spread of antibiotic resistance genes among pathogenic bacteria, the transference of genes encoding for toxins and the bacterial adaptation to environmental changes. Furthermore, they promote bacterial attachment to biotic and abiotic surfaces, interbacteria aggregation and development of biofilms in the human host (Gonzalez-Rivera et al, 2016).…”
mentioning
confidence: 99%